2019
DOI: 10.1029/2018ea000537
|View full text |Cite
|
Sign up to set email alerts
|

Response of Ionospheric Profile Parameters to Equatorial Electrojet Over Peruvian Station

Abstract: The response of the ionospheric bottomside electron density profile parameters of the F2 layer, namely, the maximum electron density (NmF2), the maximum height of F2 layer (hmF2), and bottomside thickness (B0) parameter to the equatorial electrojet (EEJ) current is examined for a Peruvian location at the Jicamarca station (12 °S, 76.9 °W) in the South American sector. The results of the analysis show that both hmF2 and B0 increase for ~2 h before sunrise and exhibit a postsunset peak during the equinoctial and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…On the other hand, the Cachimbo (SAMA boundary) station located close to the magnetic equator presented f o F 2 values less than 16 MHz during the campaign. Recently, Bello et al () presented the response of the N m F 2 , h m F 2 , and B 0 ionospheric to the Equatorial Electrojet at Jicamarca, Peru (12.0° S, 76.8° W, dip angle = −0.05°), away from the SAMA. Considering the results representing solar minimum, the authors reported that N m F 2 reach peaks of 8.8 × 10 11 electrons per m 3 (~8.5 MHz) during equinoxes, 9.5 × 10 11 electrons per m 3 (~8.8 MHz) in summer, and 5.7 × 10 11 electrons per m 3 (~6.8 MHz) in winter between 15:00 UT and 17:00 UT.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the Cachimbo (SAMA boundary) station located close to the magnetic equator presented f o F 2 values less than 16 MHz during the campaign. Recently, Bello et al () presented the response of the N m F 2 , h m F 2 , and B 0 ionospheric to the Equatorial Electrojet at Jicamarca, Peru (12.0° S, 76.8° W, dip angle = −0.05°), away from the SAMA. Considering the results representing solar minimum, the authors reported that N m F 2 reach peaks of 8.8 × 10 11 electrons per m 3 (~8.5 MHz) during equinoxes, 9.5 × 10 11 electrons per m 3 (~8.8 MHz) in summer, and 5.7 × 10 11 electrons per m 3 (~6.8 MHz) in winter between 15:00 UT and 17:00 UT.…”
Section: Resultsmentioning
confidence: 99%
“…Bello et al (2019) found significant positive correlations of EEJ and 2 m hF and of EEJ and electron density for low solar activities. This suggests the combined effect of the wind and  EB drift from E layer.…”
mentioning
confidence: 75%
“…We found that the quiet-time 2 m hF increases for ~2 hours before sunrise and peaks at postsunset during the equinoctial and summer months over Jicamarca (Bello et al, 2019). The presunrise increase is controlled by the electron density production processes by the combination of solar radiation at a high altitude near sunrise and solar zenith angle (Lee et al, 2008).…”
Section: Variability In the Height Of The Peak Of The F-layermentioning
confidence: 90%
“…In the same manner, the poleward wind that lowers the ionosphere would retard the speed of the growth of TEC near the EIA crest. Near the northern EIA crest at the Peruvian sector, the northward winds only occur at December Solstice (Figure 7h) when the F region resides at lower altitudes [41]. Thus, during the development of EIA, the TEC growth of the northern crest might be retarded, resulting in a delayed onset.…”
Section: Discussionmentioning
confidence: 99%